Safety and Immunogenicity of MF59-Adjuvanted Cell Culture–Derived A/H5N1 Subunit Influenza Virus Vaccine: Dose-Finding Clinical Trials in Adults and the Elderly. (1st March 2019) - Frey, Sharon E; Shakib, Sepehr; Chanthavanich, Pornthep; Richmond, Peter; Smith, Timothy; Tantawichien, Terapong; Kittel, Claudia; Jaehnig, Peter; Mojares, Zenaida; Verma, Bikash; Kanesa-thasan, Niranjan; Hohenboken, Matthew
Abstract: Background: A/H5N1 influenza viruses have high pandemic potential; consequently, vaccines need to be produced rapidly. MF59® adjuvant reduces the antigen required per dose, allowing for dose sparing and more rapid vaccine availability. Methods: Two multicenter, phase II trials were conducted to evaluate the safety and immunogenicity of an MF59-adjuvanted, cell culture–derived, A/H5N1 vaccine (aH5N1c) among 979 adult (18–64 years old) and 1393 elderly (≥65 years old) subjects. Participants were equally randomized to receive 2 full-dose (7.5 μg of hemagglutinin antigen per dose) or 2 half-dose aH5N1c vaccinations 3 weeks apart. Outcomes were based on Center for Biologics Evaluation Research and Review (CBER) and Committee for Medicinal Products for Human Use (CHMP) licensure criteria (titers ≥1:40 and seroconversions on day 43). Solicited reactions and adverse events were assessed (www.clinicaltrials.gov : NCT01776541 and NCT01766921). Results: CBER and CHMP criteria were met by both age groups. CBER criteria for hemagglutination titers were met for the full-dose formulation. Solicited reaction frequencies tended to be higher in the full-dose group and were of mild to moderate intensity. No vaccine-related serious adverse events occurred. Conclusions: In adult and elderly participants, the full-dose aH5N1c vaccine formulation was well tolerated and met US and European licensure criteria for pandemic vaccines.